The insulin receptor is differentially expressed in somatic and visceral primary sensory neurons - Lázár Bence András; Jancsó Gábor; Nagy István; Horváth Viktor; Sántha Péter (2018)
Recent studies demonstrated the expression of the insulin receptor (InsR) and its functional interaction with the transient receptor potential vanilloid type 1 receptor (TRPV1) in primary sensory neurons (PSNs). The present study was undertaken to reveal the target-specific expression of the InsR and its co-localization with the TRPV1 in rat PSNs. We assessed the localization of the InsR and its co-localization with the TRPV1 in PSNs retrogradely labelled with biotin-conjugated wheat germ agglutinin injected into the dorsal hind paw skin, the gastrocnemius muscle, the pancreas and the urinary bladder wall. The largest proportions of retrogradely labelled InsR-immunoreactive neurons were identified among PSNs serving the pancreas (~ 54%) and the urinary bladder (~ 53%). The proportions of retrogradely labelled InsR-immunoreactive neurons innervating the dorsal hind paw skin and the gastrocnemius muscle amounted to ~ 22 and ~ 21%. TRPV1-immunoreactive neurons amounted to ~ 63, ~ 62, ~ 67 and ~ 65% of retrogradely labelled cutaneous, muscle, pancreatic and urinary bladder PSNs, respectively. Co-localization of the TRPV1 with the InsR was observed in ~ 16, ~ 15, ~ 29 and ~ 30% of retrogradely labelled cutaneous, muscle, pancreatic and urinary bladder PSNs. These quantitative immunohistochemical data demonstrate a preponderance of InsR-immunoreactivity among PSNs, which innervate visceral targets. The present findings suggest that visceral spinal PSNs are more likely to be exposed to the modulatory effects of insulin on sensory functions, including neurotrophic, nociceptive and inflammatory processes.